Obesity is the most influential risk factor of cardiopulmonary endurance in older women - Khairani, Rita; Adriani, Donna; Amani, Patwa (Faculty of Medicine, Universitas Trisakti, 2021)
BackgroundPulmonary function decreases with age. Similarly, physical exercise capacity measured by maximal oxygen uptake, which is one indicator to measure the level of cardiac and pulmonary vascular resistance, decreases by >1% per year. This results in many respiratory diseases that occur in older persons, especially in obese older persons. Pulmonary function is a basic component of cardiopulmonary endurance, besides other factors such as age, hemodynamics, metabolism, and lifestyle. The objective of this study was to determine whether body mass index (BMI) and pulmonary function have a significant association with cardiopulmonary endurance in older women. MethodsThe study used a cross-sectional design involving 66 subjects aged 60 years and older in South Jakarta. Data was collected by measuring body mass index (BMI), pulmonary function (FEV1, FVC, FEV1/FVC) and maximal oxygen uptake (VO2 max) for cardiopulmonary endurance. Data analysis used simple and multiple linear regression tests in SPSS v.25, with p<0.05. ResultsOf the 66 older persons, 57.6% was obese. Pulmonary function of subjects showed restriction (33.3%), obstruction (6.1%) and a combination of restriction and obstruction (1.5%). Furthermore, mean VO2 max was 12.2 mL/kg/min. Multiple linear regression analysis showed a significant association of BMI and FEV1/FVC with VO2 max (Ã¢ =-0.56; 95% CI=-0.81 - (-) 0.31; p=0.000; Ã¢ =0.09; 95% CI=0.01-0.18; p=0.028). BMI was the most influential risk factor of VO2 max (Beta = -0.46). ConclusionsThere was a significant association of BMI and FEV1/FVC with VO2 max, BMI being the most influential risk factor of cardiopulmonary endurance in older women.